Effective Communication and Conflict Resolution: Family Communication of Millennial Married Couples with Different Cultures - Lusi Satia Rahmawati; Nofha Rina (Eduvest - Journal of Universal Studies, 2025)
Cross-cultural marriage in the millennial generation presents unique communication challenges, particularly in managing conflict and fostering family harmony. This study aims to explore how millennial married couples from different cultures develop communication skills for conflict resolution and adaptation. Using a qualitative phenomenological approach, this research involved ten married couples from diverse cultural backgrounds who participated in in-depth interviews. The findings reveal that effective communication skills include adapting to a partner’s communication style, employing empathy-based conflict resolution strategies, and utilizing non-verbal communication to alleviate tension. Face Negotiation Theory serves as the primary framework for understanding how couples adjust their communication to maintain relational balance. Furthermore, couples who prioritize openness, active listening, and effective emotional management tend to exhibit more harmonious and stable relationships. The implications of this study offer valuable insights for cross-cultural couples, marriage counselors, and academics seeking to understand the dynamics of family communication within the context of cultural diversity.